Collaborative computing : networking, applications and worksharing : 14th EAI International Conference, CollaborateCom 2018, Shanghai, China, December 1-3, 2018, Proceedings /: networking, applications and worksharing : 14th EAI International Conference, CollaborateCom 2018, Shanghai, China, December 1-3, 2018, Proceedings. (2019) - Unknown
No abstract available